Soluble human Suppression of Tumorigenicity 2 is associated with endoscopic activity in patients with moderate-to-severe ulcerative colitis treated with golimumab. (August 2019) - Magro, Fernando; Lopes, Susana; Silva, Marco; Coelho, Rosa; Portela, Francisco; Branquinho, Diogo; Correia, Luís; Fernandes, Samuel; Cravo, Marília; Caldeira, Paulo; Tavares de Sousa, Helena; Patita, Marta; et al.
Background: Suppressor of Tumorigenicity 2 (ST2) is an IL33 receptor detected in the mucosa and serum of ulcerative colitis (UC) patients. We evaluated soluble ST2 (sST2) as a surrogate biomarker of disease outcome and therapeutic response, in moderate-to-severe UC patients treated with golimumab. Methods: We conducted an open-label single-arm multicentre prospective study. At screening/baseline, week 6 (W6) and week 16 (W16), clinical and endoscopic activity (total Mayo score), histologic activity (Geboes index) and biomarkers were evaluated. Results: From 38 patients, 34 (89.5%) completed W6 and 29 (76.3%) completed W16. Mean age (±SD) was 34.6 ± 12.6 years; 55.9% were female. At W16, 62.1% achieved clinical response. Patients with endoscopic activity at W6 ( n = 20) had higher baseline sST2 (median, 24.5 versus 18.7 ng/ml, p = 0.026) and no decrease from baseline (median change, 0.8 versus −2.7, p = 0.029). At W6, sST2 levels correlated with endoscopic activity ( rs = 0.45, p = 0.007) but not with histological activity ( rs = 0.25, p = 0.151). The best cut-offs for endoscopic activity were sST2 = 16.9 ng/ml (sensitivity = 85%; specificity = 71%) and faecal calprotectin (FC) = 353 μg/g (sensitivity = 90%, specificity = 67%). Patients with histological activity at W6 ( n = 27) had higher baseline ST2 levels (median, 23.0 versus 13.7 ng/ml, p = 0.035). sST2 did not correlate with FC or serum C-reactive protein. FC levels correlated with histological activity and baseline FC were higher when Geboes ⩾3.1 at W6. Conclusions: sST2 may be a surrogate biomarker of UC activity and therapeutic response as it correlates with endoscopic and clinical activity at W6 of golimumab treatment, and subjects with endoscopic and histological activity at W6 had higher baseline ST2 levels.